2018
DOI: 10.21873/anticanres.12516
|View full text |Cite
|
Sign up to set email alerts
|

Combined Gemcitabine and Metronidazole Is a Promising Therapeutic Strategy for Cancer Stem-like Cholangiocarcinoma

Abstract: MNZ reduced cancer stemness in GEM-resistant CCA cells. Combined GEM and MNZ would be a promising therapeutic strategy for cancer stem-like CAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Moreover, Kawamoto et al [193] demonstrated for the first time that metronidazole (MNZ) reduces cancer stemness by reducing ALDH activity and promoting MET, resulting decreased invasive potential and enhanced gemcitabine (GEM) chemosensitivity by enhancing equilibrative nucleoside transporter 1 (ENT1) and diminishing ribonucleotide reductase M1 (RRM1) in CCA cells. Therefore, this combination therapy has the potential to improve the prognosis of CCA patients [193].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Moreover, Kawamoto et al [193] demonstrated for the first time that metronidazole (MNZ) reduces cancer stemness by reducing ALDH activity and promoting MET, resulting decreased invasive potential and enhanced gemcitabine (GEM) chemosensitivity by enhancing equilibrative nucleoside transporter 1 (ENT1) and diminishing ribonucleotide reductase M1 (RRM1) in CCA cells. Therefore, this combination therapy has the potential to improve the prognosis of CCA patients [193].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…In cholangiocarcinoma cell lines, gemcitabine-resistant cells show CSC-like phenotype, such as high ALDH activity and high CD44 expression ( Kawamoto et al, 2018 ). Metronidazole is effective for gemcitabine-resistant cells but not normal cells, although the underlying mechanism is not clear.…”
Section: Application To Diagnosis and Treatmentmentioning
confidence: 99%
“…The pattern of protein expression in two eCCA cell lines (Mz-ChA-1 and SK-ChA-1) undergoing spheroid formation has been recently investigated [121]. Compared to 2D cultures, eCCA spheroids showed an increased expression of several enzymes involved in glycolysis, hypoxia signaling, the protein ubiquitination pathway, the NADH repair pathway, and the degradation of superoxide radicals [72]. In another study, spheroids were established from the iCCA cell lines SG231, HUCCT1, CCLP1, and CCA4; their molecular characterization revealed an increased expression of key genes involved in pluripotency, self-renewal, drug-resistance, and survival, as well as stem-like surface markers [122].…”
Section: Spheroidsmentioning
confidence: 99%
“…For instance, Kawamoto et al developed spheroids from an eCCA GEM-resistant cell line (TFK-1) and from iCCA cells established from a patient with a GEM-resistant tumor. They observed that Metronidazole reduced cancer stemness features in both types of GEM-resistant CCA spheroids [72]. Cholangiosphere models were also useful for studying tumor-stroma interactions by using either direct or indirect co-culture systems.…”
Section: Spheroidsmentioning
confidence: 99%